Polypharmacy and frailty among aging World Trade Center responders - Chinmayi Venkatram; Fred Ko; Ghalib Bello; Ahmad Sabra; Hannah M. Thompson; Erin Thanik; Elena Colicino; Roberto G. Lucchini; Michael Crane; Susan L. Teitelbaum; Katherine A. Ornstein; William W. Hung (PLoS ONE, 2025)
Background During and after the 9/11 rescue and recovery efforts, World Trade Center (WTC) responders were exposed to environmental hazards that may accelerate aging and increase frailty. This study examines the relationship between polypharmacy and frailty among WTC responders to inform strategies that mitigate medication-related risks in high-risk, aging populations. Methods We included WTC responders aged 50 and older who attended at least one clinical monitoring visit at WTC Health Program between 2017–2019. Frailty was assessed using the WTC-specific Clinical Frailty Index, and associations with polypharmacy (concurrent use of 5 or more medications) and fall-risk increasing drugs (FRIDs) use were evaluated through multivariable logistic regression models adjusting for demographic, employment, health, and WTC exposure data. Results Among 6,966 WTC responders, 55% met the criteria for polypharmacy and 7.6% used FRIDs. Frailty was independently associated with both polypharmacy (OR 1.15, p < 0.001) and FRID use (OR 1.11, p < 0.001). Older age (OR 1.08, p < 0.001), obesity (OR 1.92, p < 0.001 for BMI ≥ 30), protective service occupations (OR 1.30, p = 0.002), and chronic conditions such as gastroesophageal reflux disease (OR 1.71, p < 0.001), obstructive airway disease (OR 2.24, p < 0.001), and upper respiratory disease (OR 1.85, p < 0.001) were associated with higher odds of polypharmacy. In contrast, male sex (OR 0.81, p = 0.018) and construction occupations (OR 0.73, p = 0.001) were associated with lower odds of polypharmacy. Female sex (OR 1.64, p < 0.001), smoking (current: OR 1.55, p = 0.013; former: OR 1.30, p = 0.014), and mental health conditions such as anxiety (OR 1.66, p = 0.004), depression (OR 2.85, p < 0.001), and post-traumatic stress disorder (OR 1.72, p < 0.001) were associated with higher odds of FRID use. Conclusions We found a high prevalence of polypharmacy and FRID use among aging WTC responders, with frailty significantly associated with both. Our findings underscore the need to optimize medication management for aging WTC responders, which may impact their healthy aging.